A chromatin-associated splicing isoform of OIP5-AS1 acts in cis to regulate the OIP5 oncogene. Issue 11 (2nd November 2021) - Wanowska, Elżbieta; Kubiak, Magdalena; Makałowska, Izabela; Szcześniak, Michał Wojciech
ABSTRACT: A large portion of the human genome is transcribed into long noncoding RNAs that can range from 200 nucleotides to several kilobases in length. The number of identified lncRNAs is still growing, but only a handful of them have been functionally characterized. However, it is known that the functions of lncRNAs are closely related to their subcellular localization. Cytoplasmic lncRNAs can regulate mRNA stability, affect translation and act as miRNA sponges, while nuclear-retained long noncoding RNAs have been reported to be involved in transcriptional control, chromosome scaffolding, modulation of alternative splicing and chromatin remodelling. Through these processes, lncRNAs have diverse regulatory roles in cell biology and diseases. OIP5-AS1 (also known as Cyrano ), a poorly characterized lncRNA expressed antisense to the OIP5 oncogene, is deregulated in multiple cancers. We showed that one of the OIP5-AS1 splicing forms (ENST00000501665.2) is retained in the cell nucleus where it associates with chromatin, thus narrowing down the spectrum of its possible mechanisms of action. Its knockdown with antisense LNA gapmeRs led to inhibited expression of a sense partner, OIP5, strongly suggesting a functional coupling between OIP5 and ENST00000501665.2. A subsequent bioinformatics analysis followed by RAP-MS and RNA Immunoprecipitation experiments suggested its possible mode of action; in particular, we found that ENST00000501665.2 directly binds to a number of nuclear proteins, including SMARCA4, a component of the SWI/SNF chromatin remodelling complex, whose binding motif is located in the promoter of the OIP5 oncogene.